Incorporation of Boletus edulis extract in beef burgers patties: preliminary evaluation of the antioxidant protective effects - Grangeia, Cátia (2010)
The objective of this study was to analyse the antioxidant protective effects of the incorporation of Boletus edulis extract in beef burgers. The relationship of total lipids/fatty acids to lipid peroxidation of hamburger during storage was examined. Beef burgers samples (lipids content: 15–18%) were stored for 8 days, and thiobarbituric acid reactive substances (TBARS) formation inhibition, free radical scavenging activity and reducing power were determined. The antioxidant potential increased with the amount of extract added to beef burgers, giving higher radical scavenging properties and TBARS inhibition capacity. These findings indicated that Boletus edulis extract had a protective antioxidant effect against lipid peroxidation of beef burgers patties.